Kewenangan Kepolisian Dalam Penanggulangan Tindak Pidana Pencurian Dengan Pemberatan (Curat) Melalui Operasi Sikat Agung Di Polda Bali - Ni Kadek Ayu Karin Sri Dara; Ni Putu Noni Suharyanti (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2026)
The increasing number of aggravated theft cases within the jurisdiction of the Bali Regional Police has required the police to adopt policies in exercising their authority to create public security and order. Based on this condition, the Indonesian National Police, particularly the Bali Regional Police, implemented a strategic measure through the conduct of the “Operasi Sikat Agung 2025” or “2025 Agung Clean-Up Operation”. This study aims to identify the operational mechanisms and procedures as well as to analyze the factors influencing the implementation of Operasi Sikat Agung 2025. This research employs an empirical juridical approach, in which primary data were obtained through direct interviews with officials involved in the implementation of 2025 Agung Clean-Up Operation. Secondary data were collected from statutory regulations, official police documents, and scientific publications related to aggravated theft cases. The results indicate that the implementation of this strategy was able to uncover all predetermined operational targets; however, it has not been fully optimal, as an increasing trend in aggravated theft cases still persists. The implications of this study highlight the importance of regulatory updates, strengthening the capacity of law enforcement personnel, and enhancing synergy between the police and the community in order to realize a sustainable and locally responsive crime prevention system